Three-season effectiveness of inactivated influenza vaccine in preventing influenza illness and hospitalization in children in Japan, 2013–2016 - Sugaya, Norio; Shinjoh, Masayoshi; Nakata, Yuji; Tsunematsu, Kenichiro; Yamaguchi, Yoshio; Komiyama, Osamu; Takahashi, Hiroki; Mitamura, Keiko; Narabayashi, Atsushi; Takahashi, Takao (Vaccine, 2018)
•Three-season vaccine effectiveness in preventing influenza illness was 45% (N = 12,888).•Three-season vaccine effectiveness in preventing hospitalization was 52%.•Vaccine effectiveness was highest in young group and declined with age thereafter.•Low or no significant VE was demonstrated in infants or in adolescents. We assessed the vaccine effectiveness (VE) of inactivated influenza vaccine (IIV) in children 6 months to 15 years of age in 2015/16 season. In addition, based on the data obtained during the three seasons from 2013 to 2016, we estimated the three-season VE in preventing influenza illness and hospitalization. Our study was conducted according to a test-negative case-control design (TNCC) and as a case-control study based on influenza rapid diagnostic test results. During 2015/16 season, the quadrivalent IIV was first used in Japan. The adjusted VE in preventing influenza illness was 49% (95% confidence interval [CI]: 42–55%) against any type of influenza, 57% (95% CI: 50–63%) against influenza A and 34% (95% CI: 23–44%) against influenza B. The 3-season adjusted VE was 45% (95% CI: 41–49%) against influenza virus infection overall (N = 12,888), 51% (95% CI: 47–55%) against influenza A (N = 10,410), and 32% (95% CI: 24–38%) against influenza B (N = 9232). An analysis by age groups showed low or no significant VE in infants or adolescents. By contrast, VE was highest in the young group (1–5 years old) and declined with age thereafter. The 3-season adjusted VE in preventing hospitalization as determined in a case-control study was 52% (95% CI: 42–60%) for influenza A and 28% (95% CI: 4–46%) for influenza B, and by TNCC design, it was 54% (95% CI: 41–65%) for influenza A and 34% (95% CI: 6–54%) for influenza B. We demonstrated not only VE in preventing illness, but also VE in preventing hospitalization based on much larger numbers of children than previous studies.